The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/land12010053
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Impact of Government Venture Capital on Urbanization and Its Path—Evidence from the Yangtze River Delta Urban Agglomeration in China

Abstract: Despite being the world’s largest developing country and experiencing rapid economic growth, China’s urbanization process lags behind the global standard. The comprehensive promotion of urbanization development is a critical issue for the Chinese government, with government venture capital playing a significant role in promoting regional economic development. Using urbanization dimension levels extracted through factor analysis, this study analyzes the impact of government venture capital on the urbanization d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Research on the factors influencing high-quality development is extensive, and scholars have explored the impact on regional high-quality development based on different perspectives under a single factor, under the interaction of multiple factors or under the mediating role, in order to provide countermeasure suggestions for promoting regional high-quality development from a specific area. Many scholars have found that human capital [26,27], globalization [28,29], environmental regulation [30,31], foreign investment [32][33][34], information and communication technologies [35][36][37], innovation [38,39], and finance [40][41][42] are factors that have an impact on the quality development of countries, provinces, regions and cities. In addition, some scholars have explored the impact of the interaction of multiple factors on high-quality development [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…Research on the factors influencing high-quality development is extensive, and scholars have explored the impact on regional high-quality development based on different perspectives under a single factor, under the interaction of multiple factors or under the mediating role, in order to provide countermeasure suggestions for promoting regional high-quality development from a specific area. Many scholars have found that human capital [26,27], globalization [28,29], environmental regulation [30,31], foreign investment [32][33][34], information and communication technologies [35][36][37], innovation [38,39], and finance [40][41][42] are factors that have an impact on the quality development of countries, provinces, regions and cities. In addition, some scholars have explored the impact of the interaction of multiple factors on high-quality development [43,44].…”
Section: Introductionmentioning
confidence: 99%